Breast Cancer Challenges and Screening in China: Lessons From Current Registry Data and Population Screening Studies. (22nd May 2015) - Song, Qing-Kun; Wang, Xiao-Li; Zhou, Xin-Na; Yang, Hua-Bing; Li, Yu-Chen; Wu, Jiang-Ping; Ren, Jun; Lyerly, Herbert Kim
Abstract: Background: As one of its responses to the increasing global burden of breast cancer (BC), China has deployed a national registration and BC screening campaign. The present report describes these programs and the initial results of these national BC control strategies, highlighting the challenges to be considered. Materials and Methods: The primary BC incidence and prevalence data were obtained from the Chinese National Central Cancer Registry. MapInfo software was used to map the geographic distribution and variation. The time trends were estimated by the annual percentage of change from 2003 to 2009. The description of the screening plans and preliminary results were provided by the Ministry of Health. Results: Chinese cancer registries were primarily developed and activated in the East and Coastal regions of China, with only 12.5% of the registries located in West China. Geographic variation was noted, with the incidence of BC higher in North China than in South China and in urban areas compared with rural areas. Of great interest, these registries reported that the overall BC incidence has been increasing in China, with an earlier age of onset compared with Western countries and a peak incidence rate at age 50. In response to this increasing incidence and early age of onset, BC screening programs assessed 1.46 million women aged 35–59 years, using clinical breast examinations and ultrasound as primary screening tools between 2009 and 2011. The diagnostic rate for this screening program was only 48.0/10 5 with 440 cases of early stage BC. Early stage BC was detected in nearly 70% of screened patients. Subsequently, a second-generation screening program was conducted that included older women aged 35–64 years and an additional 6 million women were screened. Conclusion: The cancer registration system in China has been uneven, with a greater focus on East rather than West China. The data from these registries demonstrate regional variation, an increasing BC incidence, and an early age of onset. The 2009 to 2011 BC screening program targeting women aged 35–59 years had a low detection rate that resulted in a second-generation screening program that extended the cohort size and ages screened to 35–64 years. Implications for Practice: Cancer registration has been active in China for decades; however, a national survey of registries has not been routinely reported. This study used MapInfo to describe the reported data and found asymmetric registration activities, geographic variations in breast cancer (BC) burdens, and an increasing incidence with a peak at age 50. The initial Chinese BC screening programs focused on a relatively young population of women aged 35–59 years and had a low detection rate, but 69.7% of patients had early stage BC. Older women were included in the second-generation screening programs, and an additional 6 million women were screened. Consideration of regional variations and age is necessary to optimize the efficiency and utility of BC screening in China, with the ultimate goal to reduce BC mortality. Abstract : The primary BC incidence and prevalence data were obtained from the Chinese National Central Cancer Registry. The 2009 to 2011 screening program targeting women aged 35–59 years had a low detection rate that resulted in a second-generation screening program that extended the cohort size and ages screened to 35–64 years.